Institutional Homogenization through McDonaldization in the Digital-Based Minimum Service Standards Reporting System (e-monev SPM) - Dio Anggara; Adelheid Pasau Tandipayuk (CV. AFDIFAL MAJU BERKAH, 2023)
Digital-based governance transformation is needed to respond to dynamic global challenges. This article aims to analyze institutional isomorphism through Mcdonaldization in a digital-based minimum service standard reporting system (e-monev SPM). Various studies show that governance needs to be dynamic, collaborative and innovative to achieve an efficient system by utilizing technological developments. In contrast to previous studies, this article argues that the transformation of governance in the reporting system for the implementation of digital-based Minimum Service Standards (e-monev SPM) indicates the occurrence of McDonaldization which is characterized by changes in rationality as a feature of modern society by utilizing technological developments that lead to the occurrence of institutional homogenization. This article uses a qualitative approach with multiple methods. Data were obtained from in-depth interviews, literature studies, secondary data, official documents and digital data. The findings of the data show the occurrence of McDonaldization in 4 (four) dimensions, namely Efficiency seen from changes in reporting mechanisms and speed, Calculability seen from the ability to be used periodically for interested parties, Predictability seen from content standardization and reporting time, and Control seen from e -monev as a digital-based tool to ensure regional compliance in reporting. The institutional homogenization efforts are indicated by the occurrence of Coercive Isomorphism related to the implementation of mandates regarding changes in the reporting system, Mimetic Isomorphism which is shown through the adoption of technology in the reporting system, and Normative Isomorphism which can be seen from organizational professionalization efforts related to increasing human resource capacity, facilities and infrastructure, cooperation, and budget. However, there is also an irrational dimension of McDonaldization rationality, which is related to the readiness of infrastructure and human resources. This article contributes to efforts to improve the quality of governance by utilizing technological developments through a digital-based reporting system .